Perancangan Website Sebagai Informasi Penjualan Sodium Cyclamat Pada PT.WIHADIL - Kurniawan, Rano; Sabalidowati, Trie Mayhera; Rahmasari, Asti; Ramadhan, Dicky; Ickhsan, Danny (LPPM UNIKA Santo Thomas, 2021)
In sales transaction, there are many methods that the company needs to compete with other competitors. Nowadays, many company use internet network or online sales to improve their sales. Online sales can improve company's sales along with high public interest in online shopping. With using online media, transaction process will be improved, integrated and increased the company's percormance. PT. Wihadil not yet using online media in business activity. This make sales was done manually and not efficient. Solution for this problem is a computerized information system. The analysis using observation method, interview method, and literature review. The system analysis report using PIECES method (Performance, Information, Economy, Control, Efficiency, and Service). The design system using object-oriented analysis method with Unified Modelling Language (UML). The purpose of the analysis is to discover sales proces and problems in PT. Wihadil. With applying online sales information system, the company can raise market opportunity, can have efficient transaction and well-integrated data sales, and can improve the service for.